A case of cervicogenic headache caused by C5 nerve root derived shwannoma: Case report. (August 2017) - Gondo, Gakuji; Watanabe, Tsuyoshi; Kawada, Junya; Tanaka, Masahiko; Yamamoto, Kazuaki; Tanaka, Satoshi; Endo, Satoshi
Introduction: We report a case of cervicogenic headache caused by an intradural extramedullary tumor of the middle cervical spine, which has not previously been reported. Case presentation: The patient was a 73-year-old male who visited a physician for a chief complaint of pain from the left lower jaw to the auricle and occipital region. The headache was induced with retroflexion of the neck. On cervical magnetic resonance imaging, an intradural extramedullary tumor was noted on the left side at the C4/5 level. The intradural tumor, which arose from the C5 nerve root, was excised and the pain was resolved. The pathological diagnosis was schwannoma. Conclusion: Previously reported cases of spinal cord tumor-induced cervicogenic headache were due to upper cervical spinal tumors. This is the first report that a middle-lower cervical intradural extramedullary tumor caused cervicogenic headache.